5-chloro-1H-indole-3-carbaldehyde 4-chlorobenzoylhydrazone - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
The amido O atom in the title molecule, C16H11Cl2N3O, is the hydrogen-bond acceptor for the amide group and amine groups of two adjacent molecules; the hydrogen-bonding interactions result in a layer motif.